Aspirin in the treatment of acute pulmonary embolism. Issue 5 (20th April 2005) - Lee, Caroline; Ferguson, Craig
Abstract : A short cut review was carried out to establish whether aspirin is a useful adjunct in the treatment of acute pulmonary embolism. No papers were found using the reported search to answer the clinical question. A clinical bottom line is stated.